Prove the identity (3secx+3cosx)(3secx-3cosx)=9(tan^2x+sin^2x).
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,544 answers
starTop subjects are Math, Science, and Business
We have to prove that (3 sec x+3 cos x)(3 sec x - 3 cos x) = 9[(tan x)^2 + (sin x)^2]
(3 sec x+3 cos x)(3 sec x - 3 cos x)
=> 9[ (1/cos x) + cos x][...
(The entire section contains 91 words.)
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Related Questions
- Prove the following identity: cos x + cos 2x + cos 3x = cos 2x(1 + 2cos x)
- 1 Educator Answer
- Prove the identity cotx*sinx=cosx/(cos^2x+sin^2x)
- 1 Educator Answer
- Prove the following identity: (1+ sin x + cos x) / (1+ sin x - cos x) = cot x/2
- 1 Educator Answer
- What is sin^2x if sinx=3cosx ?
- 1 Educator Answer
- Prove that sin^4 x+cos^4 x+(sin^2 2x)/2=1
- 1 Educator Answer
We'll manipulate the left side of the equation:
(3secx+3cosx)(3secx-3cosx) = 9(sec x)^2 - 9(cos x)^2 (difference of squares)
But sec x = 1/cos x
We'll raise to square both sides:
(sec x)^2 = 1/(cos x)^2
But 1/(cos x)^2 = 1 + (tan x)^2
9(sec x)^2 - 9(cos x)^2 = 9[1 + (tan x)^2] - 9(cos x)^2
We'll remove the brackets and we'll get:
9 + 9(tan x)^2 - 9(cos x)^2
We'll group the first and the last term:
9(tan x)^2+ 9[1 - (cos x)^2 ]
But 1 - (cos x)^2 = (sin x)^2 (Pythagorean identity)
9(tan x)^2+ 9[1 - (cos x)^2 ] = 9(tan x)^2+ 9(sin x)^2
We notice that we've started from the left side and we'll get the expression from the right side.
(3secx+3cosx)(3secx-3cosx)=9(tan x)^2+ 9(sin x)^2 = 9[(tan x)^2+ (sin x)^2]
Student Answers